Heat transfer software for local materials in Cameroon (HTSLM 1.0): simplified building energy software based on local realities - Lynda Phalone Ndjonnou Tchawa; Lucien Mandeng Mandeng; Joël Durel Tchinang Tchameu; Ramses Tanankem Menkem; Florian Kamsu Kom; Jacques Lionel Ntamag; Joseph Pondi (Discover Energy)
Abstract We report in this work the overall design of a software application for calculating the indoor temperature in a room of a building constructed from local materials in Cameroon based on heat transfer modes. This software is intended to be simplified and at a lower cost for the user. We dubbed it LOBATIN/HTSLM 1.0 for the first release. We describe the physical modeling background based on the stationary aspect of the transfer of heat flow via conduction, convection and radiation from the outside to the inside of the supposedly uninhabited building. We present how we manage Cameroon’s meteorological data to implement them in LOBATIN/HTSLM 1.0 and we compare our results with pre-existing software such as EnergyPlus. The curves obtained for hourly indoor temperatures for the chosen days in the five climatic zones defined for the software, all show a realistic bell-shaped evolution, thus prefiguring a digital decision support tool for such admitted infrastructures to be made of materials from the Local Materials Promotion Authority of Cameroon.